Tanggung Jawab Hukum Perusahaan Yang Mengalami Pailit Terhadap Kreditur Berbasis Nilai Keadilan - Jantarda Mauli Hutagalung; Dwi Atmoko (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
A Limited Liability Company (PT) is a legal entity or artificial person that is capable of carrying out legal acts through specific legal mechanism, therefore the company is also an independent legal subject that has rights and obligations in legal relations. If a company has more than one creditor, then except for creditors who have pre-emptive rights, all assets are divided fairly and proportionally among the creditors, according to the amount of receivables each creditor owes to the company. In practice, repayment of the company's obligations to its creditors is very dependent on the company's will and good faith, which in this case is carried out by the Company's Directors. There are times when a creditor gets payment first or gets a payment that is proportionally larger than other creditors. This research uses a normative juridical research method where this research uses legal norms and is supported by an approach related to events that occur in the field, which is done so that the activity process runs smoothly. The responsibilities of the Board of Directors are related to the basis of authority that a company Director has to act for and on behalf of the company. The provisions of Article 97 paragraph (4) Law Number 40 of 2007 concerning Limited Liability Companies in the event that the board of directors consists of 2 (two) or more members of the board of directors, the responsibilities as referred to in paragraph (3) apply jointly and severally to each member of the board of directors. This means that based on the words of Article 97 paragraph (4), it can be concluded that if members of the board of directors are negligent or violate their obligations to manage the company in good faith and with full responsibility, then each member of the board of directors will equally bear joint responsibility for the losses suffered by the company.